Atrophic dermatofibrosarcoma protuberans: Two case reports and literature review - Li, Yiting; Chen, Zile; Nie, Shu; Wu, Zhouwei (Frontiers in Oncology, 2023)
Dermatofibrosarcoma protuberans is a rare, locally aggressive, slowly growing cutaneous fibroblastic sarcoma with a high recurrence rate and low metastatic potential. Atrophic dermatofibrosarcoma protuberans is a rare variant usually present as atrophic plaques, easily neglected and misdiagnosed as benign lesions by patients and dermatologists. Here we report two cases of atrophic DFSP, one of which was accompanied by pigment, and review other cases have been reported in the literature. Understanding the most up-to-date literature and early identification of these DFSP variants can help clinicians avoid delayed diagnosis and improve prognosis.